Dragon Fruit (Hylocereus Polyrhizus) And Honey (Mellis) For Improving Hemoglobin Levels In Anemic Pregnant Women - Julianti, Santika; Yuliasari, Dewi; Yuviska, Ike Ate (JKM (Jurnal Kebidanan Malahayati), 2026)
Background: Anemia during pregnancy is a common health problem that can seriously affect both the mother and fetus. Non-pharmacological interventions, such as consuming iron-rich foods and vitamin C, including dragon fruit and honey, are one strategy to address this condition.Objective: This study aimed to determine the effect of dragon fruit juice (Hylocereus polyrhizus) and honey (Mellis) consumption on increasing hemoglobin (Hb) levels in anemic pregnant women.Methods: A pretest-posttest design with a control group was used. The sample consisted of 34 anemic pregnant women at Puskesmas Hajimena, South Lampung, selected through total sampling. The intervention involved daily consumption of dragon fruit juice and honey for a specified period. Data were analyzed using statistical tests to compare Hb levels before and after the intervention.Results: A significant increase in Hb levels was observed after administering dragon fruit juice and honey. Statistical analysis showed a meaningful effect on hemoglobin levels (p 0.05).Conclusion: Daily consumption of dragon fruit juice and honey significantly increases hemoglobin levels in anemic pregnant women. This natural intervention can be a safe and effective complementary strategy to prevent and treat anemia during pregnancy.Keywords: Dragon fruit, honey, anemia, pregnant women